The Effect of Urbanization on the Effectiveness of Drainage Systems and Flood Risk in Batam City - Firman Dede Hamdany; Saputra, Ade Jaya (Journal of Civil Engineering and Planning (JCEP), 2024)
Rapid urbanization in Batam City has transformed its landscape, reducing water absorption areas due to the conversion of green spaces into residential and commercial zones. This has increased surface runoff, contributing to a higher risk of flooding. This study employs a quantitative method with a survey approach and descriptive quantitative analysis of land-use and drainage system data. Spatial analysis was conducted to identify land-use changes and their impact on drainage networks. Batam's rapid economic development has brought positive benefits but also significant negative environmental impacts, as construction activities often disregard land-carrying capacity. Flooding is closely linked to urban expansion, population growth, and land demand for residential and economic purposes, which increases by 0.9% annually. The study reveals that surface water volume rises yearly due to diminished groundwater absorption capacity. To address this issue, it is recommended that the Batam City government establish stricter regulations on land use to mitigate future flood risks.